"Un orgullo de Cuba en los cielos del mundo". Cubana de aviación from Miami to Bagdad (1946–79). Issue 1 (June 2019) - Morales, Etienne
This article focuses on the transformation of the carrier Cubana de aviación before and after the 1959 Cuban revolution. By observing Cubana 's management, labour force, equipment, international passenger and freight traffic, this article aims to outline an international history of this Latin American flag carrier. The touristic air relationships between the American continent and Spain that could be observed in the 1950s were substituted – in the 1960s and 1970s – by a web of political "líneas de la amistad" [Friendship Flights] with Prague, Santiago de Chile, East Berlin, Lima, Luanda, Managua, Tripoli and Bagdad. This three-decade period allows us to interrogate breaks and continuities in the Cuban airline travel sector and to challenge the traditional interpretations of Cuban history. This work is based on diplomatic and corporative archives from Cuba, United States, Canada, Mexico, Spain and France and the aeronautical international press.